Neural correlates of affective disturbances: a comparative meta-analysis of negative affect processing in borderline personality disorder, major depressive disorder, and posttraumatic stress disorder - Schulze, Lars; Schmahl, Christian; Niedtfeld, Inga (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2019)
Background: Borderline personality disorder (BPD), major depressive disorder (MDD), and posttraumatic stress disorder (PTSD) are prominent examples of mental disorders with affective disturbances. Notably, all three disorders share a generally heightened negative affect, which is presumably the result of shared neural abnormalities in affective processing. In this meta-analysis, we aimed to identify transdiagnostic and disorder-specific abnormalities during the processing of negative compared with neutral stimuli. Methods: We synthesized neuroimaging findings of affect processing in BPD, MDD, and PTSD and calculated combined coordinate- and image-based meta-analyses. The analysis comprised 70 distinct study samples with a total of 31 unthresholded statistical parametric maps. Twenty-four studies had a focus on BPD (431 individuals with BPD, 436 healthy control subjects [HCs]), 32 studies on MDD (789 individuals with current MDD, 870 HCs), and 14 studies on PTSD (247 individuals with PTSD, 245 HCs). Results: Findings showed limbic hyperactivations in BPD and PTSD compared with limbic activation of HCs. In contrast, patients with MDD showed blunted amygdala activation in comparison with that of HCs. Additionally, the calculation of overlapping brain abnormalities in BPD, MDD, and PTSD highlighted transdiagnostic hyperactivation of the right median cingulate gyri and hypoactivation of the right middle frontal gyrus and the right middle occipital gyrus. Finally, disorder-specific comparisons also illustrate unique abnormalities for each mental disorder. Conclusions: The present results support shared and disorder-specific neural abnormalities in patients with affective disturbances.